The non-linear nature of the manifestation of conflict factors in local spaces, features of urban area of social reality - Gurzhi, Kseniia (Skhid, 2015)
The article offers a look at the such region social reality as a city. The thesis, which defines the processes taking place in the city as non-linear, it is shown that the search limits (irrational) reasons of public order operation of the urban community could fill a gap in the research explaining influence of nonlinear factors and their impact on changes in social being. It is proposed to take a look at The East conflict as the result of conflict-factors in conjunction with deterministic myth of the city, the strategies of behavior of citizens.